MARITIME ENGLISH TEACHING IN THE MIDDLE OF SEAFARER’S ISSUES AND GLOBAL MARITIME OPPORTUNITY - Sri Sartini (Universitas Ahmad Dahlan)
Indonesia is an archipelago country with thousand-pretty blessed islands with large hinterland surround. Regarding the fact, many of Indonesian believes that their ancestor is seafarer. Many Indonesian live from sea. They live from everything provided by the wealth of the seas. Fortunately, the government realizes this fact and they believe that maritime potential of country could be explored well for the sake of people’s wealth and welfare. This is done by their commitment to growing up and securing maritime higher education by following the international standard of IMO which is called as STCW 2010 Manila amendment. Data was stated that in this recent year, the world needs more than 69.241 qualified seafarers for each five years later. As the consequences, English is an obligatory to achieve. Maritime English which is more specific in the English subject would be an essential knowledge as well as skill in line with the issues. In the global maritime world, this competence should be effectively mastered by each seafarer as broad opportunity of qualified seafarers is always open for both national and international shipping companies. In this study, the writer obtain the knowledge and the data to support the paper by interviewing and sharing questionnaires to the senior seafarers who have excellent experiences at sea and in land who already signed off board from their sea projects. The results show that Maritime English teaching is absolutely needed because global maritime job opportunities in the recent year and in the future are engaging.